Highly Electrochemically‐Reversible Mesoporous Na2FePO4F/C as Cathode Material for High‐Performance Sodium‐Ion Batteries. Issue 46 (2nd October 2019) - Zhang, Jiexin; Zhou, Xi; Wang, Yunxiao; Qian, Jiangfeng; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: As promising cathode materials, iron‐based phosphate compounds have attracted wide attention for sodium‐ion batteries due to their low cost and safety. Among them, sodium iron fluorophosphate (Na2 FePO4 F) is widely noted due to its layered structure and high operating voltage compared with NaFePO4 . Here, a mesoporous Na2 FePO4 F@C (M‐NFPF@C) composite derived from mesoporous FePO4 is synthesized through a facile ball‐milling combined calcination method. Benefiting from the mesoporous structure and highly conductive carbon, the M‐NFPF@C material exhibits a high reversible capacity of 114 mAh g −1 at 0.1 C, excellent rate capability (42 mAh g −1 at 10 C), and good cycling performance (55% retention after 600 cycles at 5 C). The high plateau capacity obtained (>90% of total capacity) not only shows high electrochemical reversibility of the as‐prepared M‐NFPF@C but also provides high energy density, which mainly originates from its mesoporous structure derived from the mesoporous FePO4 precursor. The M‐NFPF@C serves as a promising cathode material with high performance and low cost for sodium‐ion batteries. Abstract : A mesoporous Na2 FePO4 F@C (M‐NFPF@C) composite derived from mesoporous FePO4 is synthesized through a facile ball‐milling combined calcination method. Benefiting from the mesoporous structure and highly conductive carbon, the M‐NFPF@C material exhibits a high reversible capacity of 114 mAh g −1 at 0.1 C, excellent rate capability (42 mAh g −1 at 10 C), and good cycling performance (55% retention after 600 cycles at 5 C).